STRATEGI PENGEMBANGAN POTENSI DESA WISATA BRAJAN KABUPATEN SLEMAN - Atmoko, T. Prasetyo Hadi (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2014)
The abundance of bamboo tree inventory in Indonesia it can be used as a new business opportunity that is promising for Brajan tourist village. To be more recognized by the public, both nationally and internationally, the need for the development of the potential in the tourist village Brajan. The purpose of this study was to determine the potential development strategies Brajan tourist village. This study used a qualitative descriptive method. Based on the research results, development of rural tourism Brajan strategy can be formulated by using SWOT and strategy alisis SO, ST, WO, WT. Strategy development potential tourist village Brajan with participatory planning in the development of tourism in the tourist village Brajan by implementing Community Based Tourism as an approach to tourism development. Keywords: Strategy Development, Potential, Tourism Village.